The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11886-017-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Remodeling and Reverse Remodeling After Myocardial Infarction

Abstract: As patients continue to live longer after myocardial infarction (MI), the prevalence of post-MI heart failure continues to rise. Changes in the left ventricle (LV) after MI involve complex interactions between cellular and extracellular components, under neurohormonal regulation. Treatments to prevent adverse LV remodeling and promote reverse remodeling in the post-MI setting include early revascularization, pharmacotherapy aimed at neurohormonal blockade, and device-based therapies that address ventricular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 82 publications
0
133
0
6
Order By: Relevance
“…Despite the diagnosis being the similar, it is seen that the process of inflammation and repair of the tissue after MI do not evoke the same response in everybody. The mechanism of harmful heart remodelling after a MI includes numerous cellular, extracellular and neurohumoral components 8 and in most cases, the size of scar formed is proportionate to the severity of heart remodelling, but it has also been demonstrated that size of scar need not translate into severe heart remodelling. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the diagnosis being the similar, it is seen that the process of inflammation and repair of the tissue after MI do not evoke the same response in everybody. The mechanism of harmful heart remodelling after a MI includes numerous cellular, extracellular and neurohumoral components 8 and in most cases, the size of scar formed is proportionate to the severity of heart remodelling, but it has also been demonstrated that size of scar need not translate into severe heart remodelling. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Beta-blockers also have anti-arrhythmic, antioxidative, anti-inflammatory, and neurohormonal regulatory effects. [25][26][27] These actions of β-blockers, beyond the hemodynamic changes, can affect cardiac remodeling, reduce the incidence of fatal arrhythmia after AMI, and improve clinical outcomes after AMI. [25][26][27] Given that the current study was not randomized, the possibility of unmeasured confounders should be considered even with the multiple sensitivity analysis.…”
Section: Beta-blocker Dose and Clinical Outcomementioning
confidence: 99%
“…In secondary prevention, their mechanism of action is unclear, but may involve reducing subsequent pathological cardiac remodelling (e.g. ventricular hypertrophy, ventricular dilation, cardiomegaly as a result of ischaemic injury) (Bhatt 2017). The benefit of beta-blockade is currently undisputed for patients with left ventricular systolic dysfunction (LVSD), however the evidence is slightly less compelling for those with preserved left ventricular function (Bangalore et al 2014;Puymirat et al 2016).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The mechanism of action of beta blockers in heart failure is poorly understood, but in addition to their ability to reduce the workload of ischaemic myocardium and inhibit arrhythmia (see above), it has been shown that they can reduce the cardiac remodelling process responsible for disease progression in heart failure (Bhatt 2017). Carvediolol, for example, may reverse the remodelling process by reducing left ventricular volumes and improving systolic function (Khattar 2003).…”
Section: Heart Failurementioning
confidence: 99%